When Social Minds Get into Trouble. (August 2016) - Kukkonen, Karin
Abstract : Fictional minds have taken a central role in cognitive narratology, from Lisa Zunshine's appropriation of the debates around so‐called 'theory of mind' (2007) to Alan Palmer's work on 'fictional minds' (2004), and, more recently, his discussion of Social Minds in the Novel (2010). Palmer brings to the fore instances in which characters think collectively, such as the 'Middlemarch mind', but he also acknowledges the possibility of interplay between externalist and internalist perspectives on fictional minds. The present article proposes to extend Palmer's discussion to include not only successful social minds but also those that get into trouble in ways interesting to narrative study. Drawing on texts by Sarah Fielding and Edward Gibbon, written in the eighteenth century, a time when the boundaries between the public and the private were renegotiated, the article develops an account of the dynamics of social minds between internalist and externalist narrative modes. It shows how these dynamics relate to the development of plot and how they come to the fore in narrative strategies, such as opaque embedded intentionalities, polyphony and irony.